OP0230 EFFICACY AND SAFETY OF TILDRAKIZUMAB, A HIGH-AFFINITY ANTI–INTERLEUKIN-23P19 MONOCLONAL ANTIBODY, IN PATIENTS WITH ACTIVE PSORIATIC ARTHRITIS IN A RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED, MULTIPLE-DOSE, PHASE 2B STUDY. (2nd June 2020) - Mease, P. J.; Chohan, S.; García Fructuoso, F. J.; Gottlieb, A. B.; Luggen, M. E.; Rahman, P.; Raychaudhuri, S. P.; Chou, R. C.; Mendelsohn, A. M.; Rozzo, S.; Orbai, A. M.
Abstract : Background: Tildrakizumab (TIL), a high-affinity anti–interleukin-23p19 monoclonal antibody, is approved to treat moderate to severe plaque psoriasis and is under investigation for treatment of psoriatic arthritis (PsA). 1 Objectives: To evaluate efficacy and safety of TIL up to week (W)52 in a randomised, double-blind, placebo-controlled, multiple-dose, phase 2b study in PsA (NCT02980692 ). Methods: Patients (pts) ≥18 years with active PsA 2 were randomised 1:1:1:1:1 to TIL 200 mg every 4 weeks (Q4W) to W52, TIL 200 mg Q12W to W52, TIL 100 mg Q12W to W52, TIL 20 mg Q12W until W24 then TIL 200 mg Q12W to W52, or placebo (PBO) Q4W until W24 then TIL 200 mg Q12W to W52. Efficacy assessments included ACR20/50/70, 75%/90%/100% improvement in Psoriasis Area and Severity Index (PASI), proportion of pts with residual minimal disease activity (MDA) response; and mean change from baseline (BL) in HAQ-DI, Leeds Dactylitis Index (LDI, pts with BL LDI ≥1), and Leeds Enthesitis Index (LEI, pts with BL LEI ≥1) to W52. Treatment-emergent adverse events (TEAEs) were monitored. Results: Of 500 pts screened, 391 were randomised and received ≥1 dose of drug. Proportions of ACR20/50/70 responders were superior with TIL vs PBO through W24; after W24 rates of responses further increased for TIL 20→200 mg Q12W and PBO→200 mg Q12W through W52 (Figure 1, 2). Other efficacy results are shown in Table. Overall from BL→W24/W25→W52, 50.4%/39.9% and 2.3%/1.0% of pts experienced a TEAE and serious AE, respectively. From BL→W24, 1 case of pyelonephritis and urinary tract infection was reported in the TIL 100 mg Q12W arm and 1 case of chronic tonsillitis was reported in the TIL 20 mg→200 mg Q12W arm. During W25→W52, 1 malignancy (intraductal proliferative breast lesion) was reported with TIL 20 mg→200 mg Q12W. No deaths or major adverse cardiac events occurred. Conclusion: TIL was well tolerated and improved joint and skin manifestations of PsA through W52. References: [1]Reich, et al. Lancet 2017;390:276−88. [2]Taylor, et al. Arthritis Rheum 2006;54:2665–73. Disclosure of Interests: Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Saima Chohan Employee of: Partner/physician at Arizona Arthritis and Rheumatology Associates, Ferran J García Fructuoso Grant/research support from: AbbVie, Eli Lilly, Gedeon Richter, MedImmune, Nichi-Iko, Pfizer, Sanofi-Aventis, Takeda, and UCB, Consultant of: AbbVie, Eli Lilly, Gedeon Richter, MedImmune, Nichi-Iko, Pfizer, Sanofi-Aventis, Takeda, and UCB, Speakers bureau: AbbVie, Eli Lilly, Gedeon Richter, MedImmune, Nichi-Iko, Pfizer, Sanofi-Aventis, Takeda, and UCB, Alice B Gottlieb Grant/research support from:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Consultant of:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Speakers bureau:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Michael E Luggen Grant/research support from: AbbVie; Amgen; Eli Lilly; Genentech; Nichi-Iko; Novartis; Pfizer; R-Pharm; and Sun Pharmaceutical Industries, Inc., Consultant of: AbbVie; Amgen; Eli Lilly; Genentech; Nichi-Iko; Novartis; Pfizer; R-Pharm; and Sun Pharmaceutical Industries, Inc., Speakers bureau: AbbVie; Amgen; Eli Lilly; Genentech; Nichi-Iko; Novartis; Pfizer; R-Pharm; and Sun Pharmaceutical Industries, Inc., Proton Rahman Grant/research support from: Janssen and Novartis, Consultant of: Abbott, AbbVie, Amgen, BMS, Celgene, Lilly, Janssen, Novartis, and Pfizer., Speakers bureau: Abbott, AbbVie, Amgen, BMS, Celgene, Lilly, Janssen, Novartis, Pfizer, Siba P Raychaudhuri Grant/research support from: AbbVie; Janssen; Novartis, Pfizer; Sun Pharmaceutical Industries, Inc, Consultant of: Amgen; Eli Lilly; Janssen; Novartis and Pfizer, Richard C Chou Consultant of: Sun Pharmaceutical Industries, Inc, Alan M Mendelsohn Shareholder of: Johnson and Johnson, Employee of: Sun Pharmaceutical Industries, Inc, Stephen Rozzo Employee of: Sun Pharmaceutical Industries, Inc, Ana-Maria Orbai Grant/research support from: Abbvie, Eli Lilly and Company, Celgene, Novartis, Janssen, Horizon, Consultant of: Eli Lilly; Janssen; Novartis; Pfizer; UCB. Ana-Maria Orbai was a private consultant or advisor for Sun Pharmaceutical Industries, Inc, not in her capacity as a Johns Hopkins faculty member and was not compensated for this service.